Immunological effects of the PE/PPE family proteins of Mycobacterium tuberculosis and related vaccines - Guo, Fangzheng; Wei, Jing; Song, Yamin; Li, Baiqing; Qian, Zhongqing; Wang, Xiaojing; Wang, Hongtao; Xu, Tao (Frontiers in Immunology, 2023)
Tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis (Mtb), and its incidence and mortality are is rising increasing. BCG vaccine came into being in the early 20th century. As the most widely vaccinated vaccine in the world, about 100 million newborns are vaccinated with BCG every year, which has saved tens of millions of lives. However, due to the differences of region and race, the average protective rate of BCG in preventing tuberculosis in children is still not high in some areas. Moreover, because the immune memory induced by BCG will weaken with the increase of age, it is slightly inferior in preventing adult tuberculosis, and BCG revaccination can not reduce the incidence of tuberculosis again.Research on the mechanism of Mtb and the development of new vaccines against TB are the main strategies for preventing and treating TB. In recent years, Pro-Glu motif-containing (PE) and Pro-Pro-Glu motif-containing (PPE) family proteins have been found to have an increasingly important role in the pathogenesis and chronic protracted infection observed in TB. The development and clinical trials of vaccines based on Mtb antigens are in progress. Herein, we review the immunological effects of PE/PPE proteins and the development of common PE/PPE vaccines.